2022
DOI: 10.48550/arxiv.2203.11954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large and Small Corrections to the JLMS Formula from Replica Wormholes

Abstract: The JLMS formula relates the bulk and boundary relative entropies and is fundamental to the holographic dictionary, providing justification for entanglement wedge reconstruction. We revisit the replica trick for relative entropy and find corrections of the JLMS formula in a variety of scenarios, even after accounting for effects of quantum extremality. We analyze the problem in the PSSY model, a model of Jackiw-Teitelboim gravity coupled to end-of-the-world branes. We find non-perturbative (in G) corrections t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…For free quantum field theories, it has been shown that this can be generalized to the sandwiched Renyi relative entropies [21] for certain values of the Renyi index. Our work in the present paper is closely related to the recent article [8] on corrections to the equality of bulk and boundary relative entropy in AdS/CFT.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…For free quantum field theories, it has been shown that this can be generalized to the sandwiched Renyi relative entropies [21] for certain values of the Renyi index. Our work in the present paper is closely related to the recent article [8] on corrections to the equality of bulk and boundary relative entropy in AdS/CFT.…”
Section: Introductionmentioning
confidence: 77%
“…To this end, we consider random tensor networks as a model of AdS/CFT [27] (i.e., tensor networks where the tensors are drawn from probability distributions). Random tensor networks have been a very useful tool for understanding features of the entanglement structure of AdS/CFT, such as the RT formula, the equality of bulk and boundary relative entropy, reflected entropy and so on [8,27,28].…”
Section: Sandwiched Renyi Relative Entropy Using Modular Operatorsmentioning
confidence: 99%